Geographic distribution, host plants, and morphological variation of the currently radiating phytophagous ladybird beetle Henosepilachna diekei. Issue 5 (9th February 2016) - Matsubayashi, Kei W.; Kahono, Sih; Fujiyama, Naoyuki; Yokoyama, Jun; Hartini, Sri; Basnagala, Suranga; Monthum, Yaowaluk; Hashim, Rosli; Katakura, Haruo
Abstract: To overview the morphological and ecological diversification within a species of phytophagous ladybird beetle Henosepilachna diekei, information concerning its distribution and host plant use was studied. This species was found widely in South East and South Asia from the Philippines through the Greater Sunda islands, a western part of Lesser Sundas, the Malay Peninsula to Sri Lanka. Mikania species (Asteraceae), Mikania micrantha in particular, were the most frequently used host plants, but some other plants belonging to Lamiaceae or Acanthaceae were also used by some local populations. Each population is possibly monophagous. According to morphological analyses, seven populations from four host plants at six sites on four Indonesian islands were grouped into two, one occurring on Java and Kalimantan (Borneo) and another on Sulawesi and Lombok, indicating that they were separated by the Wallace line. This morphological distinction was not correlated with the host plant use.